Analisis Prediksi Praktik Shenanigans Pada Laporan Keuangan - Farah Difa Aulia; M Hendri Yan Nyale (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to show directly how changes in receivables, revenue manipulation and audit committee effectiveness impact operational cash flow in publicly traded state-owned companies listed on the Indonesia Stock Exchange from 2020-2022. To understand the correlation between independent and dependent variables, this research uses quantitative methods. This study uses secondary data in the form of financial reports of publicly traded state-owned companies listed on the IDX in the 2020-2022 period by applying a purposive sampling method. There are 16 companies that can meet the criteria, resulting in a sample size of 46 data. The results of this research prove that the change in receivables variable has a negative and significant effect on operational cash flow. Meanwhile, income manipulation has a positive and significant effect on operational cash flow, and audit committee effectiveness has a positive and significant effect on operational cash flow.